Addiction and Heroin-Assisted Treatment: Legal Discourse and Drug Reform. (September 2019) - Boyd, Susan; Norton, Alexa
This article analyzes the arguments put forth over a 3-day period at an injunction hearing, Providence Health Care Society v. Canada, held March 13–15, 2014 in Vancouver, British Columbia. The plaintiffs sought broad interlocutory relief from the Court for the provision of prescription heroin if requested by their physicians. This article fills an identified gap in scholarship by analyzing the civil Charter challenge, including the notice of civil claim, injunction court transcripts, judgment, and individual plaintiffs' affidavits. We draw from Canada's unique history of drug prohibition and critical drug research to contextualize our analysis and findings. We argue that the lives of people using criminalized drugs, such as heroin, are affected by legal realms that produce ideas about heroin, addiction, and criminality that ultimately impact public health policies and treatment initiatives.